PENGARUH PENERAPAN SELF ASSESSMENT SYSTEM TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN KEGIATAN USAHA DAN PEKERJAAN BEBAS (STUDI EMPIRIS TERHADAP WAJIB PAJAK ORANG PRIBADI DI KOTA DENPASAR) - Ni Putu Ayu Siska Wulantari; I Made Endra Lesmana Putra (UNHI Press, 2020)
Tax reforms that include efforts to improve the taxation system and mechanism, including a tax payment and reporting system that fully authorizes the Taxpayer to determine, calculate and report the amount of tax owed annually in accordance with the provisions of existing taxation laws, which known as the self assessment system. The purpose of this study is to prove empirically that the application of the Self Assessment System affects the compliance of individual taxpayers who carry out business activities and free work in the city of Denpasar. Researchers use Regression Analysis as a method of data analysis, data collection is done by observation, interviews, literature studies, and questionnaires. The initial stage in the analysis is to test the validity and reliability of research instruments. The results showed that the application of the self assessment system had a positive effect on the compliance of individual taxpayers who carry out business activities and free work in the city of Denpasar.